2017
DOI: 10.17113/ftb.55.04.17.5128
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Storage Time, Temperature and Type of Packaging on Release of Phthalate Ester into Packed Acidic Juice

Abstract: SummaryAcidic liquids such as verjuice, lemon juice and vinegar are frequently consumed in Iran. Different kinds of acidic liquids are packaged in polyethylene terephthalate (PET) and high--density polyethylene (HDPE) bottles. There is evidence indicating that phthalates can leach from PET and HDPE bottles into their contents. In this work the effect of storage time, temperature and bottle type on the migration of phthalates from packaging materials into acidic liquids is studied by analyzing the samples store… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 23 publications
5
14
0
Order By: Relevance
“…In the study by Jandlová, Jarošová and Kameník (2017) was found in these plastic bags average DBP concentration of 22.47 μg.g -1 plastic and average DEHP concentration of 11.76 μg.g -1 plastic.…”
Section: Materials and Methodsologymentioning
confidence: 78%
“…In the study by Jandlová, Jarošová and Kameník (2017) was found in these plastic bags average DBP concentration of 22.47 μg.g -1 plastic and average DEHP concentration of 11.76 μg.g -1 plastic.…”
Section: Materials and Methodsologymentioning
confidence: 78%
“…We were looking for some similar research to our research for better comparison, but we did not find any similar research with concentrations of phthalates in yoghurt enriched with flour or fiber. In study by Rastkari et al, (2017), where they examined the transfer of phthalates from PET and HDPE into the acidic fluid during storage (0, 2, 4 and 6 months of measurement), the DEHP concentration increased with time in the liquids, the DBP concentration increased to 2 months, then dropped in the packaged fluid. In Schecter et al, (2013) study, the average concentration of DEHP was determined at 144 ng•g -1 and the average concentration of DBP was determined at 104.4 ng•g -1 in the category "other dairy products" purchased in New York, this category included yoghurt.…”
Section: Resultsmentioning
confidence: 99%
“…In the study (Rastkari et al, 2017) was examined the migration of phthalic acid esters -dibutyl phthalate and di-(2-ethylhexyl) phthalate too -from wrapping to acidic liquids -vinegar, lemon juice, verjuice. The phthalate concentrations in acidic liquids with longer storage time increased.…”
Section: Discussionmentioning
confidence: 99%